Integrasi Midtrans Payment Gateway pada Website E-Commerce Hafiz Cell - Agil Dwi Anugra; Muhammad Nasir; M. Izman Herdiansyah; Irman Effendy (PPPM Institut Teknologi Pagar Alam, 2025)
Digital transformation is pushing retailers to adopt online platforms. Hafiz Cell’s offline operations limit market reach and transactional efficiency. This study aims to design and develop an e-commerce website for Hafiz Cell with Midtrans Payment Gateway to enable automated, secure, real-time transactions. The development method uses Extreme Programming (XP), which includes planning, design, coding, and testing. The system is built with Laravel 10 and supported by MySQL for data storage, Cloudinary for media management, and RajaOngkir for shipping cost estimation. Implemented features include product management, cart, checkout, automatic payments through Midtrans (QRIS, e-wallets, bank transfer, credit cards), and an admin dashboard. Black-Box Testing across core modules (homepage, profile, catalog, cart, checkout, payment, order history, and admin pages) shows all scenarios work as expected. The implementation improves transaction efficiency, reduces recording errors, and expands market reach through 24/7 availability. These results indicate that the combination of Laravel and Midtrans, together with XP, is effective for building a functional, production-ready e-commerce system for SMEs.